2019
DOI: 10.1186/s12875-019-1046-0
|View full text |Cite
|
Sign up to set email alerts
|

Young people with attention deficit hyperactivity disorder in transition from child to adult services: a qualitative study of the experiences of general practitioners in the UK

Abstract: BackgroundMany young people with Attention Deficit Hyperactivity Disorder (ADHD) have impairing symptoms that persist into adulthood, yet only a minority experience continuity of care into adult life. Despite growing emphasis on the primary care role in ADHD management in NICE ADHD and transition guidance, little is known about GPs’ perspectives, which could hamper efforts to improve outcomes for young people leaving children’s services. This study aimed to understand GPs’ experiences of involvement with this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
7
33
0
Order By: Relevance
“…Several young people had not had their medication reviewed since leaving CAMHS, and were unsure about whether they were receiving the correct dosage or whether they should still be taking their medication. This finding mirrors the results of a qualitative study exploring the role of GPs in prescribing ADHD medication for young people after CAMHS, with some GPs unsure if they had the appropriate expertise to prescribe specialist medication without support from secondary care (37).…”
Section: Discussionsupporting
confidence: 75%
“…Several young people had not had their medication reviewed since leaving CAMHS, and were unsure about whether they were receiving the correct dosage or whether they should still be taking their medication. This finding mirrors the results of a qualitative study exploring the role of GPs in prescribing ADHD medication for young people after CAMHS, with some GPs unsure if they had the appropriate expertise to prescribe specialist medication without support from secondary care (37).…”
Section: Discussionsupporting
confidence: 75%
“…Reasons for not prescribing include concerns regarding the diagnosis, the unavailability of non-pharmacological treatment, and potential inadequacy of physical monitoring in secondary care ( 102 ). Primary care practitioners also voice concerns around the nature of medication in terms of stimulants being “controlled drugs,” and risk of potential misuse and diversion ( 103 ), they may lack confidence in managing ADHD treatment, due to knowledge limitations, insufficient training and/or poor communication from specialist services ( 104 ). In a survey of 150 General Practitioners (GPs), 64% stated that they would be likely to change their views on prescribing with clearer advice from specialists, and 67% said they would be influenced if there was a clear protocol for monitoring a child on medication ( 104 ).…”
Section: Results and Consensus Outcomementioning
confidence: 99%
“…In these instances, poor information flow and communication by secondary care may have a negative impact on the care provided by GPs. 34 'Recurvisity' defined by Rogers et al describes how future demand for services and the process of help-seeking is determined by a patient's previous experiences. 35 In line with this, the current study identified that prior negative experiences of consulting GPs affected young people's future help-seeking.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Most, however, do not meet the strict eligibility criteria for adult services, 7 and therefore are discharged to their GP. 8 GPs may feel ill-equipped to provide the right care for these young people, 9 for example, prescribing certain types of psychotropic medication without input from specialist care. 10 As mental health care from GPs is often the only available health service for young people it is important that the experiences and needs of young people are identified to improve care for young people with mental health problems in primary care.…”
Section: Introductionmentioning
confidence: 99%